Pengembangan Media Pembelajaran Fisika Berbasis Game Edukasi: Analisis Bibliometrik Menggunakan Software VOSViewer (2017-2022) - Rahmawati, Yulika; Febriyana, Monica Merry; Bhakti, Yoga Budi; Astuti, Irnin Agustina Dwi; Suendarti, Mamik (Jurnal Penelitian Pembelajaran Fisika, 2022)
Physics is one of the abstract subjects that require visualization so that learning media is needed so that students are able to understand the concepts studied. One of the learning media that displays visualization by utilizing technology in the form of educational games. This study aims to analyze the development of educational game learning media in physics learning with a bibliometric approach using VOSViewer software. The method used in this study is bibliometric analysis. There are 6 clusters of classification through VOSViewer software. The results of the study obtained articles used with the title "educational games" and "learning media", as well as the keyword "physics learning" began to increase rapidly in 2018, 2019, 2020, and 2021. The article was produced from various universities in Indonesia and uses Indonesian. In this study, 4 clusters were obtained that discussed the topic of developing educational game learning media in physics learning. For the topic of developing educational game learning media, it has been quite widely done, but for the topic of the effectiveness of the use of educational games in physics learning, it is still rare for a study to be carried out.Keywords: educational games, learning media, physics learning, bibliometric, vosviewer.